2014
DOI: 10.1016/j.clinbiomech.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Plantarflexor muscle function in healthy and chronic Achilles tendon pain subjects evaluated by the use of EMG and PET imaging

Abstract: (2014). Plantarflexor muscle function in healthy and chronic Achilles tendon pain subjects evaluated by the use of EMG and PET imaging. Clinical Biomechanics, 29,[567][568][569][570] Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.sciencedirect.com: http://dx.doi.org/10. 1016/j.clinbiomech.2014.03.003 This is the final text version of the article, and it may contain minor differences from the journal's pdf ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Regions that were identified as having greater uptake were generally in areas that would have a greater proportion of connective tissue relative to contractile proteins. Previous research has shown that glucose uptake in the Achilles tendon during isometric tasks is lower compared with the triceps surae muscles . This would suggest that we should have seen lower relative uptake in these areas, while in fact they were greater.…”
Section: Discussionmentioning
confidence: 65%
“…Regions that were identified as having greater uptake were generally in areas that would have a greater proportion of connective tissue relative to contractile proteins. Previous research has shown that glucose uptake in the Achilles tendon during isometric tasks is lower compared with the triceps surae muscles . This would suggest that we should have seen lower relative uptake in these areas, while in fact they were greater.…”
Section: Discussionmentioning
confidence: 65%
“…Isometric Strength. Small to moderate effect sizes were reported in 2 studies, 45,48 indicating reduced isometric PF strength in those with AT (Hedges g ¼ 0.46-0.78). These effect sizes equated to a reduction of 5% to 12% between the symptomatic and asymptomatic sides or between the symptomatic side and asymptomatic controls.…”
Section: Maximal-strength Profilementioning
confidence: 99%
“…A total of 13 studies 11,19,[40][41][42][43][44][45][46][47][48][49][50] included both male and female participants, whereas 6 studies 13,39,[51][52][53][54] included men only. The authors of 8 studies 13,39,42,43,[48][49][50][51] compared strength measures between symptomatic and asymptomatic participants, the authors of 8 studies 11,40,41,[44][45][46][47]52 compared strength values between injured and uninjured sides of the same participants, and the authors of 4 studies 48,[53][54][55] compared strength variables between the injured and uninjured sides of the same participant and between the injured side and asymptomatic participants. Strength values between the ''most'' and ''least'' symptomatic sides were compared in 1 study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although both methods measure muscle activation from their own perspective, the results will not necessarily correlate with each other. However, some attempts to compare the methods have been done (39,40,41,54), but the results have not been shown to be consistent.…”
mentioning
confidence: 99%